Kurikulum Pendidikan Karakter di Taman Kanak-kanak Negeri Pembina Semarang - Darmu’in, Darmu’in (Nadwa, 2013)
The character education curriculum in Pembina Public Kindergarten Sema-rang was initiated since 2010 in the form of socializing ideas, internships at kindergarten Budi Mulia 2 Yogyakarta, testing, curriculum development: mapping the character values, aligning the vision, mission, and educational goals. The character values include: religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, the spirit of natio-nalism, patriotism, respect for achievement, friendly, peace-loving, fond of reading, environmental care, social care , as well as responsibilities. The as-sessment of character education is done through observing students and ex-pressed in a qualitative statement. The simulation results of the character education assessment show that the majority of students (67.93%) have had a character (MK), others (23.82%) have begun to develop (MB), a small amount (6.50%) began to appear (MT), and the rests have not seen yet (1.14%) (CB).